Sustainable Archaeological Heritage: An Interactive Museum for Teki̇rdağ - Seher Selin Özmen; Esen Gökçe Özdamar (Yüzüncü Yıl Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)

(untitled)
This article explores the significance of cultural heritage conservation and archaeological heritage in sustainable development, focusing on Tekirdağ, Turkey’s region with a rich archaeological heritage. Turkey faces threats like rapid urbanization, smuggling, terrorism, war, and climate change, which pose challenges to protecting archaeological materials. Museums play a vital role in understanding and preserving cultural heritage sustainably. They act as public spaces that contribute to urban identity and raise awareness through exhibitions and educational programs. Archaeological museums, specifically, have the potential to promote cultural tourism and support economic development by attracting tourists and creating job opportunities for local communities. This article discusses the possibility of a contemporary and sustainable archaeological museum in Tekirdağ, addressing the weaknesses of the city's existing museums. In this context, the article focuses on the museum proposal incorporating contemporary architecture, interactive exhibition techniques, and technological innovations like augmented reality and virtual tours for Tekirdağ. In the second part of the article, the design of an interactive archeological museum for Tekirdağ is presented based on the proposals of architecture students at Tekirdağ Namık Kemal University. Design proposals show that these advancements would make the visitor experience more engaging and accessible, showcasing the city’s past and contributing to education, culture, and tourism to preserve its heritage for future generations.